2020
DOI: 10.1089/bioe.2020.0014
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Electrostatic Interactions for Drug Delivery to the Joint

Abstract: Arthritis is a debilitating joint disease with a high economic burden and prevalence. There are many challenges delivering therapeutics to the joint, including low bioavailability when administered systemically and low joint retention after intra-articular injection. Therefore, drug delivery systems such as nanoparticles, liposomes, dendrimers, and carrier proteins have been utilized to overcome some of these limitations. To enhance joint tissue localization and retention, there are opportunities to leverage e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 138 publications
(177 reference statements)
1
8
0
Order By: Relevance
“…Interestingly, PEGylation of G1 and G2 BPL molecules did not significantly affect their uptake by cartilage (Figure 2b,d,e), which suggests that the PEGylated BPL molecules possess the optimal surface charge required for cartilage adhesion and penetration. These observations are consistent with previous studies which suggested that the transport of cationic nanocarriers across the cartilage tissue is associated with an optimal surface net charge 11,15,20,24,33 …”
Section: Resultssupporting
confidence: 93%
“…Interestingly, PEGylation of G1 and G2 BPL molecules did not significantly affect their uptake by cartilage (Figure 2b,d,e), which suggests that the PEGylated BPL molecules possess the optimal surface charge required for cartilage adhesion and penetration. These observations are consistent with previous studies which suggested that the transport of cationic nanocarriers across the cartilage tissue is associated with an optimal surface net charge 11,15,20,24,33 …”
Section: Resultssupporting
confidence: 93%
“…In addition, the constituent monomers of Aggrecan contain a large number of negatively charged carboxyl residues and sulfate residues, allowing cationic biomaterials to be attracted to the joints by electrostatic forces 162 . Utilizing this unique property, nanoparticles with a positive charge tend to target the ECM and increase the uptake of chondrocytes through electrostatic attraction 162 . A well-designed green fluorescent protein (GFP) was used to probe the optimal range of positive charge 163 .…”
Section: Targeted Biomaterials In Osteoarthritismentioning
confidence: 99%
“…Electrostatic interaction causes charged molecules to be adsorbed physically on oppositely charged carriers (Abraham et al, 2020;Kaasalainen et al, 2015;Kumar and Sharma, 2020;Liu et al, 2018;Mauri et al, 2017;Sims et al, 2020;Xiao et al, 2013;Zhao et al, 2012). This strategy has been widely used for gene delivery, where DNA and RNA are negatively charged and carriers positively charged (Nayerossadat et al, 2012;Sung and Kim, 2019;Zhang et al, 2016).…”
Section: Non-covalent Interactionsmentioning
confidence: 99%